COVID-19 and The Implementation of QawÄ’id Fiqhiyyah in E-Commerce - Bambang Suhada; Agus Alimuddin; Lisda Aisyah (Justicia Islamica, 2020)
The COVID-19 Pandemic has implications for all aspects of life, having both positive and negative impacts. The positive impact can be interpreted by finding a maslahat in contemporary studies by considering mafÄsid and maá¹£Äliá¸¥ maps. Meanwhile, the negative impact of one of them is the collapse of economic conditions. By examining the positive impact of COVID-19 and maslahat theory, it can be attributed to the rule of Law (qawÄ'id fiqhiyyah) resulting in changes in the frame of the rule of Law, as well as in efforts to produce a maá¹£laá¸¥ah, iá¹£lÄá¸¥, and istiá¹£lÄá¸¥. This study aims to examine the benefit of contemporary business development and the implications of qawÄ'id fiqhiyyah on contemporary business development during the COVID-19 Pandemic. The study uses qualitative research to look at every event and then link it with fiqh's study as a library research approach. Patterns and interpretation results are presented in a descriptive form to have more structured and readable. The contemporary study found six basic fiqh rules as a foundation for business implementation through e-commerce, changes in mafÃ¢sid maps. It produced maá¹£Ã¢liá¸¥ making business through e-commerce as a platform for business development to realize prosperity. The study has implications on Islamic law studies' expansion and novelty in contemporary issues and brought prosperity to the Islamic economy during the COVID-19 Pandemic.Pandemi COVID-19 berimplikasi pada seluruh aspek kehidupan, yakni aspek yang mendatangkan dampak positif maupun negatif. Dampak positif dapat dimaknai dengan menemukan maslahat dalam kajian kontemporer dengan melakukan pertimbangan terhadap peta mafÄsid dan maá¹£Äliá¸¥. Sedangkan dampak negatif salah satunya dengan runtuhnya kondisi perekonomian. Dengan mengkaji dampak positif COVID-19 dan teori maslahat dapat dikaitkan dengan kaidah hukum (qawÄ’id fiqhiyyah) sehingga menghasilkan perubahan dalam bingkai kaidah hukum, termasuk juga dalam upaya menghasilkan sebuah maá¹£laá¸¥ah, iá¹£lÄá¸¥ dan istiá¹£lÄá¸¥. Kajian ini bertujuan mengkaji kemaslahatan yang terjadi dalam pengembangan bisnis kontemporer serta implikasi qawÄ’id fiqhiyyah terhadap pengembangan bisnis kontemporer di masa pandemi COVID-19. Metode yang digunakan dalam penulisan ini yaitu riset kualitatif yang melihat setiap kejadian lalu mencoba menghubungkan dengan kajian fiqih sebagai pendekatan kepustakaan (library research), pola dan hasil interpretasi yang dilakukan selanjutnya disajikan dalam bentuk deskriptif agar lebih terstruktur dan memiliki tingkat keterbacaan. Kajian kontemporer yang dilakukan menemukan enam dasar kaidah fiqih sebagai landasan dalam pelaksanaan bisnis melalui e-commerce, perubahan peta mafÃ¢sid dan maá¹£Ã¢liá¸¥ yang dihasilkan menjadikan bisnis melalui e-commerce sebagai wadah pengembangan bisnis untuk mewujudkan kesejahteraan. Kajian yang dilakukan berimplikasi pada perluasan dan kebaruan kajian hukum Islam dalam permasalahan kontemporer dan mendatangkan kesejahteraan dalam perekonomian Islam di masa Pandemi COVID-19.